Ultrasound features and molecular diagnosis testing of thyroid mass - Ismael, Nadhum J. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Thyroid gland is one of the most important glands in human body due to the necessary hormones it produces. It can be afffeced by different types of infections and diseases, one of the most risky abnormalities of this gland is thyroid masses. The aim of this study is to find how does thyroid masses start from the molecular stages and is there any relation with it and genetics, for this purpose we scanned more than 273 patients by ultrasound from different ages groups, and genders, thyroid mass detected in 17 of them, 3 with cystic fluid filled mass, and 14 with solid mass . Blood samples from thes patients were analysed and molecular study were performed by taking exon 11 and 15 from Braf gene mution was detected in all patients included frame shift mutaion a deletion of adenine in same position , while no sequence variation was found in the exon 11 Braf gene. In conclusion According to DNA sequence analysis, genomic variation was not found in exon 11 of the BRAF gene in all patients, an exonic alteration was detected in exon 15 in 7 patients was deletion of (A) in coding nucleotide , which the BRAF mutational hot spot region are found. The result of the deletion mutation is conversion of all of codons after deletion